2007
DOI: 10.1021/bi061965j
|View full text |Cite
|
Sign up to set email alerts
|

Isolated CP1 Domain of Escherichia coli Leucyl-tRNA Synthetase Is Dependent on Flanking Hinge Motifs for Amino Acid Editing Activity

Abstract: Protein synthesis and its fidelity rely upon the aminoacyl-tRNA synthetases. Leucyl-(LeuRS), isoleucyl-(IleRS) and valyl-(ValRS) tRNA synthetases have evolved a discrete editing domain called CP1 that hydrolyzes the respective incorrectly misaminoacylated noncognate amino acids. Although active CP1 domain fragments have been isolated for IleRS and ValRS, previous reports suggested that the LeuRS CP1 domain required idiosyncratic adaptations to confer editing activity independent of the full-length enzyme. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…The Nand C-terminal ␤-strands of the CP1 domains were fused to the Rossmann fold of M. mobile LeuRS at Glu-229 and Gly-232 (⅐⅐⅐ 224 WIGKEEIDG 232 ⅐⅐⅐), respectively. This corresponds to Glu-228 and Ala-362, the naturally occurring E. coli LeuRS fusion sites that link the flexible ␤-strands of the CP1 domain to the Rossmann fold (19,25).…”
Section: Resultsmentioning
confidence: 99%
“…The Nand C-terminal ␤-strands of the CP1 domains were fused to the Rossmann fold of M. mobile LeuRS at Glu-229 and Gly-232 (⅐⅐⅐ 224 WIGKEEIDG 232 ⅐⅐⅐), respectively. This corresponds to Glu-228 and Ala-362, the naturally occurring E. coli LeuRS fusion sites that link the flexible ␤-strands of the CP1 domain to the Rossmann fold (19,25).…”
Section: Resultsmentioning
confidence: 99%
“…The first coarse sieve, an aminoacylation active site that is located in an ancient canonical core of the aaRS, is responsible for activating amino acids. A second fine sieve, a hydrolytic active site, has been clearly demonstrated to correct the enzyme's mistakes in a number of synthetase systems (27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introduction: Aminoacyl-trna Synthetase Fidelitymentioning
confidence: 99%
“…1A) (20). Although the LeuRS CP1 domain is best known for its role in proofreading or editing misacylated tRNA Leu (21,22), genetic rescue experiments identified splicing sensitive sites within and around the CP1 domain (9,23). We had also shown that the isolated CP1 domain from ymLeuRS stimulated bI4 intron RNA splicing in vivo (17).…”
mentioning
confidence: 84%
“…1B) extends from Ile-260 to Glu-431. Previously we showed that the ␤-strands are required for deacylation of mischarged tRNA in the E. coli enzyme (21). Thus, we constructed a CP1-containing fragment that included the ␤-strands, extending from Trp-238 to Leu-446 (CP1-␤; Fig.…”
Section: Isolated Ymcp1 Domain Splices In Vitro Unlike Its E Colimentioning
confidence: 99%
See 1 more Smart Citation